Network diagrams for diagnosing the spike skill in significance of some kinematical and anthropometric variables and the number of points for the best spiker participating in the Olympic volleyball of Beijing, 2008 - Abdu Khalifa Mahrous, A. (World Journal of Sport Sciences, 2010)
This study aims to identify some of the kinematical and anthropometric variables and the most appropriate points to the spike skill in volleyball. It also aims to set benchmark levels for some kinematical and anthropometric variables, the number of hitting points for volleyball players performing the spike skill in volleyball, as well as develop a graphic network in terms of some kinematical and anthropometric variables, the number of hitting points for volleyball players performing the spike skill in volleyball. A sample of the best 10 players performing the spike skill was intentionally selected, participated in the Beijing Olympics (2008), with the highest direct number of points for spike. Successful attempts were counted to each player, the 10 players, which were valid for analysis and the choice of three attempts for each player and analyzing it in terms of time. Data regarding the players' height, age and the number of points obtained were obtained through the official website of the Beijing Olympics (2008). The author used MAXTRAQ for the time analysis for the skill in question. The author used SPSS version 16 for the following data: the mean, standard deviation, upper and lower limits, range, skewness and the equation to find the fixed amount to convert the raw scores to standard scores (Six Sigma Score). Based on the statistical treatment followed by the author, the results revealed that the scores corresponding to the percentile degrees to the player's height, ranging between 212.90 and182.90cm, age between 36.73 and 16.47 years, weight between 113.53 and 61.07 kg, maximum height between 382.87 and 327.33 cm, total time of skill between 2.36 and 3.15 seconds, the approach time between 0.57 and 1.22 seconds, the takeoff time between 0.047 and 0.007 seconds, flight and hitting time between 1.69 and 1.47 seconds, the landing time between 0.374 and 0.152 seconds. Values of average height 197.90 cm, age 27.10 years, weight 87.30 kg, the maximum height 355.10 cm, total time 2.75 seconds and the time of each phase (approach 0.89, take off 0.027, hitting 1.58, landing 0.263) are the values appropriate to get the highest points of the spike in volleyball of the Beijing Olympics (2008).